Mapping and modelling the geographical distribution of soil-transmitted helminthiases in Peninsular Malaysia : implications for control approaches - Romano, Ngui; Aziz, Shafie; Kek, Heng Chua; Mohd S., Sitam; Hesham M., Al-Mekhlafi; Wan W., Wan Sulaiman; Rohela, Mahmud; Yvonne Ai, Lian Lim (PAGEPress®, Pavia, Italy, 2014)
Soil-transmitted helminth (STH) infections in Malaysia are still highly prevalent, especially in rural and remote communities. Complete estimations of the total disease burden in the country has not been performed, since available data are not easily accessible in the public domain. The current study utilised geographical information system (GIS) to collate and map the distribution of STH infections from available empirical survey data in Peninsular Malaysia, highlighting areas where information is lacking. The assembled database, comprising surveys conducted between 1970 and 2012 in 99 different locations, represents one of the most comprehensive compilations of STH infections in the country. It was found that the geographical distribution of STH varies considerably with no clear pattern across the surveyed locations. Our attempt to generate predictive risk maps of STH infections on the basis of ecological limits such as climate and other environmental factors shows that the prevalence of Ascaris lumbricoides is low along the western coast and the southern part of the country, whilst the prevalence is high in the central plains and in the North. In the present study, we demonstrate that GIS can play an important role in providing data for the implementation of sustainable and effective STH control programmes to policy-makers and authorities in charge.